2013
DOI: 10.1007/s12038-012-9287-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the DNA damaging effects of amitraz on human lymphocytes in the Comet assay

Abstract: Amitraz is formamidine pesticide widely used as insecticide and acaricide. In veterinary medicine, amitraz has important uses against ticks, mites and lice on animals. Also, amitraz is used in apiculture to control Varroa destructor. It this study, the alkaline Comet assay was used to evaluate DNA damaging effects of amitraz in human lymphocytes. Isolated human lymphocytes were incubated with varying concentrations of amitraz (0.035, 0.35, 3.5, 35 and 350 mu g/mL). The Comet assay demonstrated that all concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 42 publications
2
20
1
Order By: Relevance
“…It is known that plant-derived soft acaricides have a very low potential of honey bee intoxication in contrast to other acaricides that were reported to exert toxic effects on bees, as in the case of amitraz [24], coumaphos [25], fl uvalinate [26], formic acid [27] and oxalic acid [17]. Besides, plant-derived soft acaricides do not contaminate hive products, opposed to other acaricides that have been proven to leave residues: oxalic and formic acid [14] fl uvalinate and coumaphos, amitraz and chlorfenvinphos [28] and pose risk to consumers of bee products [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that plant-derived soft acaricides have a very low potential of honey bee intoxication in contrast to other acaricides that were reported to exert toxic effects on bees, as in the case of amitraz [24], coumaphos [25], fl uvalinate [26], formic acid [27] and oxalic acid [17]. Besides, plant-derived soft acaricides do not contaminate hive products, opposed to other acaricides that have been proven to leave residues: oxalic and formic acid [14] fl uvalinate and coumaphos, amitraz and chlorfenvinphos [28] and pose risk to consumers of bee products [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic acaricides such as coumaphos (organophosphate), tau-fl uvalinate, fl umethrine (pyrethroid) and amitraz (formamidine) were widely used in the last decades with variable effi cacy. Their residues accumulate inside the hive and could exhibit negative effects on bees and brood [6] and contaminate their products [7] with potential health risk to consumers [8,9]. Moreover, due to the repeated use of these substances, mite populations develop resistance to pyrethroids (fl uvalinate and fl umethrin), but also to coumaphos and, in less extent, to amitraz [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…As no single explanation for the extensive colony losses has been identified, it is concluded that many biological and environmental stressors, acting alone or in combination, can lead to premature colony mortality (vanEngelsdorp et al 2009, Genersch 2010. Along with bee diseases, many problems in beekeeping are caused by chemicals used against honey bee pathogens, whose appliance is accompanied by side effects on bees and brood (Pettis et al 2004a, 2004b, Loucif-Ayad et al 2008, contamination of bee products (Bogdanov 2006) and health risk to beekeepers and bee product consumers (Stanimirovic et al 2005, Stevanovic et al 2008, Radakovic et al 2013. Therefore, it would be benefitial if some harmless naturalbased supplements could provide maintaining healthy and strong honey bee colonies and help in prevention of their mortality.…”
Section: Honey Bees Apis Mellifera L (Hymenopteramentioning
confidence: 99%
“…Nonetheless, the efficacy of this practice in controlling ectoparasites is unpredictably conditioned by numerous variables such as the concentration of molecules, the frequencies of spraying and their residual effect in the environment and on dogs [9]. In addition, toxicity for both personnel and animals represents a major concern for this strategy [10,11]. Recently, a combination of 10% imidacloprid and 4.5% flumethrin (Seresto®, Bayer Animal Health) has been developed for use in dogs and cats in a polymer matrix collar [12,13].…”
Section: Introductionmentioning
confidence: 99%